The incidence of myocardial infarction and stroke in head and neck cancer patients - Hyun-Keun Kwon (Nature Portfolio, 2021)
Abstract Various treatment modalities are used for head and neck cancer (HNC). This study analyzed the incidence and risks of myocardial infarction (MI) and stroke by cancer site and treatment modality in 22,737 patients newly diagnosed with HNC registered in the Korean National Health Insurance Service database in 2007–2013. An additional 68,211 patients without HNC, stroke, or MI were identified as the control group. The risks for MI (hazard ratio [HR] = 1.38, 95% confidence interval [CI] 1.24–1.53), stroke (HR = 1.48, 95% CI 1.37–1.60), and mortality (HR = 5.30, 95% CI 5.14–5.47) were significantly higher in the HNC group. Analysis by cancer site showed the risk of MI and mortality was highest in hypopharynx cancer, while the risk of stroke was highest in nasopharynx and paranasal sinus cancer. Analysis by treatment modality showed the highest risks for MI (HR = 1.88, 95% CI 1.31–2.69) and mortality (HR = 2.95, 95% CI 2.75–3.17) in HNC patients receiving chemotherapy (CT) alone, while HNC patients receiving CT with surgery had the highest risk for stroke (HR = 1.81, 95% CI 1.14–2.88). Careful attention to MI and stroke risks in HNC patients is suggested, especially those who received both CT and radiotherapy.